Clinical and investigational study for the aetiological evaluation of patients in nontraumatic altered sensorium and its outcome - Jali, Siba Narayan; Nayak, Sachida Nanda; Alexander, Biju K.; Tripathy, Diptimayee; Behera, Bijaya K. (International Journal of Research in Medical Sciences, 2019)
Background: Apart from head injury many patients present to the tertiary care hospital in unconscious state, the etiology of which is obscure in most of the cases. The present study was conducted with on objective to provide insight into the clinical features and diagnostic methods to know the aetiology of patients with non-traumatic cases of altered sensorium and to study the outcome of these patients. Methods: This is an observational study on 100 patients of altered sensorium of non-traumatic origin during the period from October 2012 to September 2014 conducted in the Department of General Medicine, MKCG Medical College Hospital, Berhampur, Odisha, India. All patients were selected for the study based on the inclusion exclusion criteria. Detailed history, clinical evaluation, laboratory investigations like neuroimaging studies etc. were carried out. Statistical data analysis was done using Graph pad Prism 6 and Microsoft Excel. P value <0.0001 was considered statistically extremely significant. Results: Out of 100 patients of altered sensorium, 64 were males and 36 were females. All patients were in the age group of 19 to 89 years. Cerebrovascular accident was the most common aetiology of altered sensorium followed by metabolic encephalopathy and infection. Altered sensorium in patients with CVA carries a high mortality. Metabolic causes and younger age indicated a better prognosis, patients with low (Glasgow Coma Score) GCS score of 3 to 4 had poorer prognosis. Conclusions: The results suggest that clinical assessments yield accurate predictive information about the potential for recovery in cases of altered sensorium. So, this study concludes that empirically based estimates of prognosis in the neurologically severely ill provides great reassurance to those involved in a decision-making process, including patients’ families and physicians.